Uji Konstruk Validitas dan Reliabilitas Instrumen Pengukuran Pengunaan Media Sosial, Kesehatan Mental dan Perilaku Kesehatan Reproduksi pada Remaja: Construct Validity and Reliability Testing of Instruments Measuring Social Media Use, Mental Health, and Reproductive Health Behaviors in Adolescents - Nurul Jannah; Lubna Nada Mufidah; Margaretha Maria Shinta Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2026)
The use of social media among adolescents has surged rapidly in the digital era and has the potential to impact their mental health and reproductive health behaviors. Therefore, valid and reliable instruments are needed to assess these relationships. This study aims to examine the construct validity and reliability of five instruments: the Youth Social Media Engagement Scale (YSMES), Adolescent Anxiety Screening Inventory (AASI), Youth Self-Concept Assessment Scale (YSCAS), Adolescent Sleep Quality Index (ASQI), and Adolescent Reproductive Health Behavior Scale (ARHBS) in measuring social media engagement, anxiety, self-concept, sleep quality, and reproductive health behaviors among adolescents. A cross-sectional design with a stratified cluster sampling technique was employed, involving 208 adolescents aged 13–18 years. Construct validity was analyzed using confirmatory factor analysis (CFA), while internal reliability was assessed using Cronbach’s alpha. CFA results showed χ²/df values between 1.72 and 1.90, CFI between 0.94 and 0.96, TLI between 0.93 and 0.95, and RMSEA between 0.052 and 0.058, indicating that all instruments have good validity. Cronbach’s alpha values for YSMES = 0.89, AASI = 0.87, YSCAS = 0.88, ASQI = 0.86, and ARHBS = 0.90 confirm high internal reliability. Thus, all instruments are valid and reliable for measuring social media use, mental health, and reproductive health behaviors among adolescents. Abstrak Penggunaan media sosial pada remaja meningkat pesat di era digital dan berpotensi memengaruhi kesehatan mental serta perilaku kesehatan reproduksi mereka. Oleh karena itu, diperlukan instrumen yang valid dan reliabel untuk menilai hubungan tersebut. Penelitian ini bertujuan menguji validitas konstruk dan reliabilitas lima instrumen: : Youth Social Media Engagement Scale (YSMES), Adolescent Anxiety Screening Inventory (AASI), Youth Self-Concept Assessment Scale (YSCAS), Adolescent Sleep Quality Index (ASQI), dan Adolescent Reproductive Health Behavior Scale (ARHBS) dalam mengukur keterlibatan media sosial, kecemasan, konsep diri, kualitas tidur, dan perilaku kesehatan reproduksi pada remaja. Desian Penelitian cross-sectional dengan tehnik sampling stratified cluster ini melibatkan 208 remaja berusia 13–18 tahun. Validitas konstruk dianalisis menggunakan confirmatory factor analysis (CFA), sedangkan reliabilitas internal dievaluasi dengan Cronbach’s alpha. Hasil CFA menunjukkan nilai χ²/df 1,72–1,90, CFI 0,94–0,96, TLI 0,93–0,95, dan RMSEA 0,052–0,058, mengindikasikan seluruh instrumen memiliki validitas yang baik. Cronbach’s alpha untuk YSMES = 0,89, AASI = 0,87, YSCAS = 0,88, ASQI = 0,86, dan ARHBS = 0,90, menegaskan reliabilitas internal yang tinggi. Dengan demikian, seluruh instrumen dinyatakan valid dan reliabel untuk mengukur penggunaan media sosial, kesehatan mental, dan perilaku kesehatan reproduksi pada remaja.